2019
DOI: 10.3762/bjnano.10.186
|View full text |Cite
|
Sign up to set email alerts
|

Oblique angle deposition of nickel thin films by high-power impulse magnetron sputtering

Abstract: Background: Oblique angle deposition is known for yielding the growth of columnar grains that are tilted in the direction of the deposition flux. Using this technique combined with high-power impulse magnetron sputtering (HiPIMS) can induce unique properties in ferromagnetic thin films. Earlier we have explored the properties of polycrystalline and epitaxially deposited permalloy thin films deposited under 35° tilt using HiPIMS and compared it with films deposited by dc magnetron sputtering (dcMS). The films p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 62 publications
2
8
0
Order By: Relevance
“…We also showed that oblique deposition is more decisive in the definition of the anisotropy direction than application of an in-situ magnetic field for inducing uniaxial magnetic anisotropy. Also for polycrystalline Py films oblique deposition by HiPIMS presents a lower coercivity and anisotropy field than when dcMS deposition is applied [32][33][34]. While none of the above mentioned results verify self-shadowing they are consistent with our interpretation of the order i.e.…”
Section: Introductionsupporting
confidence: 60%
“…We also showed that oblique deposition is more decisive in the definition of the anisotropy direction than application of an in-situ magnetic field for inducing uniaxial magnetic anisotropy. Also for polycrystalline Py films oblique deposition by HiPIMS presents a lower coercivity and anisotropy field than when dcMS deposition is applied [32][33][34]. While none of the above mentioned results verify self-shadowing they are consistent with our interpretation of the order i.e.…”
Section: Introductionsupporting
confidence: 60%
“…We also showed that oblique deposition is more decisive in definition of anisotropy direction than application of an in-situ magnetic field for inducing uniaxial magnetic anisotropy. Also for polycrystalline Py films oblique deposition by HiPIMS presents a lower coercivity and anisotropy field than when dcMS deposition is applied [32][33][34]. While none of the above mentioned results verify self-shadowing they are consistent with our interpretation of the order i.e.…”
Section: Introductionsupporting
confidence: 56%
“…Since then, different properties of the magnetic films obtained by GLAD have been studied: the magnetic domain structure [ 16 , 17 , 18 , 19 ], the magnetic anisotropy [ 20 , 21 , 22 , 23 ], the magneto-resistance [ 24 , 25 , 26 ], the optical and magneto-optical behaviors [ 27 , 28 ], and even their possible use for information storage [ 29 , 30 , 31 ]. Nevertheless, only a few of those studies refer to arrays fabricated by MS-GLAD [ 19 , 25 , 31 , 32 , 33 ]. The specific deposition method used is important not only for future application development, as indicated above, but mainly because the deposition regime differs.…”
Section: Introductionmentioning
confidence: 99%